Area vs. density: influence of visual variables and cardinality knowledge in early number comparison - Abreu-Mendoza, Roberto A.; Soto-Alba, Elia E.; Arias-Trejo, Natalia (Frontiers in Psychology, 2013)
Current research in the number development field has focused in individual differences regarding the acuity of children’s Approximate Number System. The most common task to evaluate children’s acuity is through non-symbolic numerical comparison. Efforts have been made to prevent children from using perceptual cues by controlling the visual properties of the stimuli (e.g. density, contour length and area); nevertheless, researchers have used these visual controls interchangeably. Studies have also tried to understand the relation between children’s cardinality knowledge and their performance in a number comparison task; divergent results may in fact be rooted in the use of different visual controls. The main goal of the present study is to explore how the usage of different visual controls (Density, Total filled area, and Correlated and anti-correlated area) affects children’s performance in a number comparison task, and its relationship to children’s cardinality knowledge. For that purpose, 77 preschoolers participated in three tasks: 1) Counting List Elicitation to test whether children could recite the counting list up to ten, 2) Give a Number to evaluate children’s cardinality knowledge, and 3) Number Comparison to evaluate their ability to compare two quantities. During this last task, children were asked to point at the set with more geometric figures when two sets were displayed on a screen. Children were exposed only to one of the three visual controls. Results showed that overall, children performed above chance in the Number Comparison task; nonetheless, Density was the easiest control, while Correlated and anti-correlated area was the most difficult in most cases. Only Total filled area was sensitive to discriminate Cardinal Principal knowers from Non-Cardinal Principal knowers. How this finding helps to explain conflicting evidence from previous research, and how the present outcome relates to children’s number word knowledge is discussed.